KONSEP ISLAMISASI ILMU MOHD KAMAL HASSAN - nabil amir, ahmad; Tasnim Abdul Rahman (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2025)
The paper examines the idea of Islamization of human knowledge as formulated by Professor Dr. Mohd. Kamal Hassan (1942-2023). It aims to survey its thoughtful and lasting impact as reflected in the context of his inspiring moral, spiritual and religious ideal that influence intellectual tradition and meyaphysical consciousness and contemporary landscape of educational policy and practice in Malaysia. The philosophy and conceptual framework of Islamization of knowledge he developed was realized in the curriculum and policies of the International Islamic University Malaysia, whose structural formation and ideology was enshrined in the University’s constitution since its establishment in 1983. The study is based on qualitative method, in the form of literature review and documentary survey. The data were scientifically analyzed using descriptive, analytical, historical and synthesis framework to make an objective and acccurate finding. The finding shows that Prof. Kamal has made an important and influential impact in gearing the ideas of tawhidic worldview, through his inspiring works that planned and implemented the principle of Islamization of knowledge in Malaysia. The study contributes to highlight his consequential and unprecedented concept and holistic approaches in introducing a comprehensive theory and values of tawhid and its cultural manifestation through the theory of Islamization (Islamiyyatul ma‘rifat), integration of knowledge and values (takamul al-ma‘rifi), comprehensive excellence and Islamicization that help to reset the current context and progress of education and intellectual life in Malaysia.